Engaging patients and family members in the evaluation of a mental health patient portal: protocol for a mixed-methods study. Issue 8 (23rd August 2018) - Strudwick, Gillian; Kuziemsky, Craig; Booth, Richard G; Collins, Sarah; Chyjek, Anna; Sakal, Moshe; Harris, Alexandra; Strauss, John
Abstract : Introduction: Twenty per cent of Canadians will experience a mental illness in any year. Mental health patient portals have been developed to support these individuals in taking more control over their own mental health and care. This may be done through electronic access to their health records and other supportive functions like completion of online self-assessments. To date, there has been limited research into the value that these portals may provide within mental health contexts. This study will identify what value mental health patient portals may offer to patients and their family members. Methods and analysis: This study will use a mixed-methods design. Patients will complete a survey consisting of validated instruments at the time of enrolment in the portal, and at 3 and 6 months of portal use. Patient and family member focus groups will be conducted. Portal usage data will be collected to identify if there are differences in outcomes based on usage. The study will be done at Canada's largest mental health and addiction teaching hospital, and will be conducted using a patient and family-oriented research approach, engaging these important representatives in all stages of the research process. The primary data analysis for the survey portion of the study will be done using linear mixed-effect models, assessing the differences between patients with different portal usage levels. A thematic analysis will be conducted of the focus group transcripts. Ethics and dissemination: Approval from the study site's Research Ethics Board has been obtained. The dissemination of findings of this study will be done through presentations at conferences, as well as a formal peer-reviewed journal article. Additionally, the research team will work with a group of patients and family members to identify opportunities to complete knowledge translation and dissemination activities in non-traditional venues.